Peningkatan Hasil Belajar Siswa Smk Pada Materi Reaksi Redoks Menggunakan Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) di Kelas X TEI-C SMKN 1 Cimahi - Diah Marliana (Journal on Education, 2020)
This study aims to improve student learning outcomes at Cimahi 1 State Vocational School Using the cooperative learning model type Student Team Achievement Division (STAD). The research method in this research is classroom action research (CAR) which consists of two cycles. The research subjects were 37 students of class X TEC-C SMKN 1 Cimahi on redox reaction material. The results of this study indicate the ability of students of class X TEI-C SMK 1 Cimahi can be improved through STAD support. This can be seen from the results of the initial test cycle II obtained a minimum value of 75 increased by 22.0% with an average value of 70.1 and from cycle II to cycle II increased by 15.9% with an average value of 75.4. Then it can be saud that in cycle II the learning scenario has been said ti be successful.